Bibliometric and visualized analysis of fertility preservation in patients with gynecological malignancies from 2014 to 2023 - Li, Zhanghuan; Du, Wenqi; Qin, Yufei; Yang, Yinghui; Gao, Yuxia; Yang, Jing; Feng, Xiaojie; Fan, Wenqiang; Wang, Wenxiang (Clinical Surgical Oncology, 2025)
Fertility preservation in patients with gynecological malignancies (FP-GM) has gained increasing attention. This study conducts a bibliometric analysis of FP-GM research, aiming to identify key themes, influential publications, major contributors, and emerging trends that have shaped the field over the last decade. Data were sourced from the Web of Science Core Collection (WOSCC). Tools such as CiteSpace and VOSviewer were utilized to conduct a detailed bibliometric analysis, focusing on keyword co-occurrence, citation bursts, collaboration networks, and clusters of influential references. A total of 2029 original articles were identified, involving 11446 authors from 342 countries and 8693 institutions, and published across 417 academic journals. Annual Publication generally shows an increasing trend. The USA is leading much of the advancement in this field. The International Journal of Gynecological Cancer published the most articles, and the journal with the most citations was Fertility and Sterility. Grynberg, Michael was the author with the most publications, and Donnez, J was the author with the most citations. The most frequently occurring keywords were “fertility preservation”, “cancer”, “women” and “chemotherapy”. Clusters of references including “cryopreservation techniques”, “ovarian cancer”, “cervical cancer”, “endometrial cancer” and so on. Citation bursts underscored the impact of guidelines and experimental research on the evolution of FP-GM. Research on FP-GM is dominated by cryopreservation techniques and the reproductive consequences of cancer treatments. Influential guidelines and experimental research have shaped the field, with emerging interest in fertility-sparing treatments and hormonal preservation strategies, indicating a continuous evolution in clinical practices. •First bibliometric analysis on fertility preservation in gynecologic oncology (FP-GM) from 2014 to 2023.•Identifies key themes, influential authors, and emerging research trends in FP-GM.•Highlights the USA as a leading contributor, with robust global collaborations.•Guides future research by mapping core research areas and collaboration networks in FP-GM.